GHARAR DALAM PERSPEKTIF EKONOMI ISLAM : TINJAUAN LITERATUR GLOBAL - Sri Wahyuni Ginting (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study examines the concept of gharar in Islamic economics as a form of uncertainty and excessive risk in contracts, which may undermine the principle of transactional justice. Employing a qualitative approach, the research is conducted through a literature review of ten scholarly articles published between 2013 and 2024, retrieved via Google Scholar with Scopus and Web of Science serving as the primary sources of reference. The analysis reveals that gharar practices remain prevalent, both within Islamic financial institutions and in individual transactions, thereby affirming the continued relevance of this issue in contemporary Islamic economic practices. Consequently, the study emphasizes the necessity of systematic efforts to avoid ambiguity and excessive risk in contractual agreements, in order to uphold justice and legal certainty in Islamic economic transactions at both national and global levels.